FIGURES 33–40. Adults. 33 in The Hadeninae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park, USA 2380 - Pogue, Michael G. (Zenodo, 2010)
FIGURES 33–40. Adults. 33, Melanchra adjuncta, m, Virginia, Montgomery Co.; 34, Melanchra assimilis, m, Canada, Newfoundland, Doyles, Codroy Valley, 8 July 1959, D.C. Ferguson; 35, Polia detracta, m, North Carolina, Haywood Co., Purchase Knob, 4924 ft., 8 June 2002, J. Adams, USNMENT 00153850; 36, Polia detracta, m, Tennessee, Sevier Co., Campsite 20, 2520 ft., 22 June 2004, M.G. Pogue, USNMENT 00220921; 37, Polia detracta, m, North Carolina, Swain Co., 15.2 mi NE GSMNP ent. on 441, Deep Creek Trail, 4815 ft., 8 June 2003, M.G. Pogue, USNMENT 00155420; 38, Polia imbrifera, m, North Carolina, Haywood Co., Polls Gap, Rough Fork Trail, 5140 ft., 28 June 2004, M.G. Pogue, USNMENT 00221234; 39, Polia nimbosa, m, North Carolina, Swain Co., 5.6 mi SW of Jct. 441 & Clingmans Dome Rd., Noland Divide Trail, 5950 ft., 28 July 2003, M.G. Pogue, USNMENT 00156519; 40, Polia nimbosa, m, Tennessee, Sevier Co., 1.3 mi W of Jct. 441 & Clingmans Dome Rd., Road Prong Trail, 28 July 2003, M.G. Pogue, USN- MENT 00156574. Published as part of Pogue, Michael G., 2010, The Hadeninae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park, USA 2380, pp. 1-75 in Zootaxa 2380 (1) on page 62, DOI:10.11646/zootaxa.2380.1.1, http://zenodo.org/record/5312376